CARDIOVASCULAR EVENTS AND TARGET ORGAN DAMAGE IN PRIMARY ALDOSTERONISM: A SYSTEMATIC REVIEW AND META-ANALYSIS. (June 2018) - Monticone, S.; D'Ascenzo, F.; Moretti, C.; Williams, T.A.; Veglio, F.; Gaita, F.; Mulatero, P.
Abstract: Objective: According to some reports, patients affected by primary aldosteronism (PA) have an increased risk of cardio- and cerebrovascular complications compared to patients with essential hypertension (EH). However, current available evidence relies on highly heterogeneous studies. We aimed to assess the relationship between PA and major adverse cardiac and cerebrovascular events, cardiac target organ damage, diabetes and metabolic syndrome by integrating results of previous studies. Design and method: We performed a meta-analysis of both prospective and retrospective observational studies to investigate the association between PA and stroke, coronary artery disease (as co-primary end points), atrial fibrillation and heart failure (as secondary endpoints), target organ damage, metabolic syndrome and diabetes, in comparison with patients affected by essential hypertension. We also compared PA subtypes, aldosterone producing adenoma (APA) and bilateral adrenal hyperplasia (BAH). Results: A total of 31 studies, including 3838 patients with primary aldosteronism and 9284 patients with essential hypertension were included in the analysis. After a median of 8.8 years from hypertension diagnosis, compared with patients with essential hypertension, patients with primary aldosteronism displayed an increased risk of stroke (odds ratio [OR] 2.58, 95% CI 1.93–3.45), coronary artery disease (1.77, 1.10–2.83), atrial fibrillation (3.52, 2.06–5.99), and heart failure (2.05, 1.11–3.78). Similarly, the risk of diabetes (OR 1.33, 95% CI 1.01–1.74), metabolic syndrome (1 53, 1 22–1 91), and left ventricular hypertrophy (2.29, 1.65–3.17) was increased in patients affected by PA compared with EH. Conclusions: An early diagnosis of PA is important because affected patients display an enhanced cardiovascular risk compared to patients with EH.